Pengaruh Produk Domestik Regional Bruto (PDRB) Terhadap Tingkat Kemiskinan Di Provinsi Sumatera Utara Tahun 2011-2020 - Novriyanti Zebua, Tety (CV RIFAINSTITUT, 2022)
The local government plays an important role in alleviating poverty, especially in the province of Sumatera Utara which consists of 34 districts/cities. The large number of poor people who do not get a decent life is a concern for local governments to overcome this. Various programs of national development activities are carried out by the government to improve people's welfare. One of them is the development program to the regions so that the program is able to increase development growth so that it can be seen that the gross value added of all goods and services created by an area arising from economic activity can be seen. The purpose of this study is to find out how much influence the value of the regional gross domestic product (GRDP) has on the poverty level in Sumatera Utara Province. The results showed that the Gross Regional Domestic Product (GRDP) had a negative and significant effect on the poverty level in Sumatera Utara Province.